Bilingual lexicography, an example of an African language : lari. - (:unkn) unknown (My University, 2017)
This thesis is to study the lexicography of the lari, who is the third language of the Republic of the Congo, in order to propose the creation of a lari-french bilingual dictionary. The first chapter to understand the history of the ethnic group Balari and location and demographic of the language today. The second chapter is an analysis of the language on the morphological, phonetic, grammatical and lexicographical plan. The third chapter is dedicated to the proposals for the drafting of the lari-french bilingual dictionary.
Keywords: African Research